Evaluation of Self-Directed Learning in Nursing Students: A Systematic Review and Meta-Analysis - Mohammad Nazarianpirdosti (Hindawi Limited, 2021)
Background. Self-directed learning plays an important role in nursing education and is associated with academic achievement, communication self-efficacy, assertiveness, responsibility, and students’ clinical competencies. This study was conducted to analyze the existing research on the level of self-directed learning in nursing students. Methods. In this systematic review and meta-analysis, all studies that had examined the level of self-directed learning in nursing students until March 2, 2020, were searched in Science Direct, Ovid, Scopus, PubMed, ProQuest, Web of Science, and Google Scholar databases. In the meta-analysis section, I2 index and the random effects model were used. Comprehensive Meta-Analysis software (version 2) was used for data analysis. Results. The mean score of self-directed learning in 12 articles with 3830 samples was 156.73 ± 1.47 out of 200 (95% CI: 153.3–160.1). These scores were 153.50 ± 2.71 (95% CI: 148.18–158.82) and 154.67 ± 1.32 (95% CI: 157.50–159.32) in the male and female students, respectively. There was a significant relationship between self-directed learning and sample size, year of study, and semester (p<0.05). Conclusion. The mean self-directed learning in nursing students was at a moderate level, which does not seem to be sufficient. Given the positive role of self-directed learning in nursing education, it is essential that nursing professors teach self-directed learning skills to students via training courses.